Hazard Management in Karang Hawu Beach, Sukabumi Distric, West Java: MANAJEMEN BAHAYA DI KAWASAN WISATA PANTAI KARANG HAWU, KABUPATEN SUKABUMI, JAWA BARAT - Utami, Sofia Ucu; Muntasib, E. K. S. Harini; Samosir, Agustinus M. (Media Konservasi, 2019)
Karang Hawu Beach, obtained its name from its furnace-shaped coral, is one of the leading tourist attraction in Palabuhanratu, Sukabumi, West Java. The distinctive natural panorama is having a reefs jutting into the sea,has attracted many visitors, up to 1.7 million of visitors per year. It is related to great tourist attraction but it often couses so many accidents that come from a lot of dangers in this attraction. This research, aimed to analysis and potential hazard mapping and management hazard recommendation. The method used was identification which is then analyzed and evaluated through UNEP (2008) and mapping using the ArcGis 10.3 application. Hazard risk in Karang Hawu Beach consist of phisical hazard such as ocean waves, coastal currents, tides, tsunamis and earthquakes. Biological hazard such as reef, sea urchin, and jellyfish. Hazard management in that area were managed by a lot of stakeholders such as Balawista, government institutions and communities around Karang Hawu Beach, under the supervision of the Tourism Department, Culture and Sports in Sukabumi Regency. The results of the analysis showed that coastal currents and waves have the highest potential hazard. Risk and hazard management were recomended such as avoiding risk. Management development is carried out socially and institutionally by increasing the understanding of potential hazards in the Karang Hawu Beach tourist area. Technical steps that must be taken to reduce risk include providing first aid, using red flags to mark the dangerous areas, increasing visitor awareness of hazards, and establishing safe areas for visitors. Keywords: awareness, hazard, hazard management, Karang Hawu beach, technical measures